PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL, KINERJA LINGKUNGAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fidella Alysia Putri; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2025)
Firm value reflects a company’s achievements and the level of public trust in the company. Additionally, firm value serves a key reference for investor in assessing investment feasibility. The study aims to examine to impact of institutional ownership, environmental performance, and firm size on firm value.The research employs a quantitative approach using secondary data obtained from company annual report and determination letters issued by the Kementerian Lingkungan Hidup dan Kehutanan (KLHK). The collected data is analyzed using multiple regression analysis to evaluate the relationship between the studied variables. The study population consist of basic materials sector company listed on the Indonesia Stock Exchange (IDX) from 2020-2023. Using a purposive sampling technique, a total of 72 samples were selected from 29 companies that met the research criteria.The findings indicate that institutional ownership and environmental performance have no significant effect on firm value. Meanwhile, firm size is proven to have a significant effect on firm value.